2022
DOI: 10.1002/marc.202200385
|View full text |Cite
|
Sign up to set email alerts
|

Automated Design of Li+‐Conducting Polymer by Quantum‐Inspired Annealing

Abstract: Automated molecule design by computers is an essential topic in materials informatics. Still, generating practical structures is not easy because of the difficulty in treating material stability, synthetic difficulty, mechanical properties, and other miscellaneous parameters, often leading to the generation of junk molecules. The problem is tackled by introducing supervised/unsupervised machine learning and quantum-inspired annealing. This autonomous molecular design system can help experimental researchers di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…For example, there are potentially more than 10 60 types of structures for organic compounds, but regular computers cannot explore each candidate in a reasonable time. [20][21][22][23] Exploring an ideal material structure, X, with a given parameter, y, is called an inverse problem. 23,24 It has become easy to construct a normal prediction model y = f (X) with conventional machine learning models implemented in, for example, scikit-learn libraries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are potentially more than 10 60 types of structures for organic compounds, but regular computers cannot explore each candidate in a reasonable time. [20][21][22][23] Exploring an ideal material structure, X, with a given parameter, y, is called an inverse problem. 23,24 It has become easy to construct a normal prediction model y = f (X) with conventional machine learning models implemented in, for example, scikit-learn libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Third, extensive forward prediction with different structures X takes a long time due to the astronomical number of candidates, and thus the exploration space must be carefully reduced. 20,21 Several algorithms have been proposed to solve inverse problems for materials. Deep reinforcement learning searches for suitable structures that satisfy specic target properties, and these algorithms are oen developed for organic molecules, especially drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using charge-transfer (CT) polymer materials as battery electrolytes was first introduced in the patent literature . The three-part combination of polymer with electron-donating groups, small-molecule organic electron acceptors, and salt was reported to achieve surprisingly high ionic conductivity (10 –4 S/cm at room temperature). , Later, Oyaizu and co-workers reported that an array of small-molecule charge-transfer complexes mixed with lithium salt also exhibited elevated ionic conductivity (10 –6 to 10 –4 S/cm at room temperature) . The authors hypothesized that fast ion transport occurs at the interfaces between the charge-transfer crystals and salt.…”
mentioning
confidence: 99%
“…To overcome this difficulty posed by the combinatorial explosion, quantum annealing (QA), an operation type of quantum computers, and QA-inspired methods have attracted attention. , Actually, QA can solve combinatorial optimization problems known as quadratic unconstrained binary optimization (QUBO) much faster and more accurately than classical computers because, in principle, QA can evaluate all combinations simultaneously using the quantum tunnelling effect and the quantum superposition. , It has been used in problems related to biology, machine learning, and materials science . Also, information and communication technology have been applied to optimize the combinations.…”
mentioning
confidence: 99%
“… 7 , 9 It has been used in problems related to biology, 10 machine learning, 11 and materials science. 12 Also, information and communication technology 13 have been applied to optimize the combinations. This feature has inspired us to use this method to elucidate surface states with adsorption.…”
mentioning
confidence: 99%